Genome-wide screening of lectin putative genes from Sorghum bicolor L., distribution in QTLs and a probable implications of lectins in abiotic stress tolerance - Makarim El-fadil M. Osman; Amina Ibrahim Dirar; Emadeldin Hassan E. Konozy (BMC Plant Biology, 2022)
Abstract Background Sorghum bicolor is one of the most important crops worldwide with the potential to provide resilience when other economic staples might fail against the continuous environmental changes. Many physiological, developmental and tolerance traits in plants are either controlled or influenced by lectins; carbohydrate binding proteins. Hence, we aimed at providing a comprehensive in silico account on sorghum’s lectins and study their possible implication on various desired agronomical traits. Results We have searched sorghum’s genome from grain and sweet types for lectins putative genes that encode proteins with domains capable of differentially binding carbohydrate moieties and trigger various physiological responses. Of the 12 known plant lectin families, 8 were identified regarding their domain architectures, evolutionary relationships, physiochemical characteristics, and gene expansion mechanisms, and they were thoroughly addressed. Variations between grain and sweet sorghum lectin homologs in term of the presence/absence of certain other joint domains like dirigent and nucleotide-binding adaptor shared by APAF-1, R-proteins, and CED-4 (NB-ARC) indicate a possible neofunctionalization. Lectin sequences were found to be preferentially overrepresented in certain quantitative trait loci (QTLs) related to various traits under several subcategories such as cold, drought, salinity, panicle/grain composition, and leaf morphology. The co-localization and distribution of lectins among multiple QTLs provide insights into the pleiotropic effects that could be played by one lectin gene in numerous traits. Conclusion Our study offers a first-time inclusive details on sorghum lectins and their possible role in conferring tolerance against abiotic stresses and other economically important traits that can be informative for future functional analysis and breeding studies.